2009
DOI: 10.3724/sp.j.1005.2009.00101
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of ancient tea gardens and tableland tea gardens from Yunnan Province as revealed by AFLP marker

Abstract: This study was conducted to evaluate the genetic diversity within and among the plants of four ancient tea gardens and two tableland tea gardens form Yunnan Province, China by AFLP technique. The percentage of polymorphic loci (P) of the plants from six tea gardens was 92.31%. The genetic diversity within the six gardens demonstrated by Nei cents genetic diversity (He) was estimated to be 0.1366, while Shannon indices (Ho) were 0.2323. The percentage of polymorphic loci of the four ancient tea populations was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 3 publications
0
7
0
1
Order By: Relevance
“…However, human activities are the additional factors that have been impacting the genetic diversity of tea plants and the adverse effects of encroachment of humans are increasing continuously. Felling the wild trees of C. taliensis to collect leaves for producing the wild tea (Figure 1c) [24,26] and further deforestation to make way for farming, grazing and construction have caused persistent and serious damage to natural sources of this tea plant [43]. The lower genetic diversity and the higher F values in the wild populations may indicate the stronger genetic drift due to these causes (Table 2, Figure 5 and Additional file 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, human activities are the additional factors that have been impacting the genetic diversity of tea plants and the adverse effects of encroachment of humans are increasing continuously. Felling the wild trees of C. taliensis to collect leaves for producing the wild tea (Figure 1c) [24,26] and further deforestation to make way for farming, grazing and construction have caused persistent and serious damage to natural sources of this tea plant [43]. The lower genetic diversity and the higher F values in the wild populations may indicate the stronger genetic drift due to these causes (Table 2, Figure 5 and Additional file 2).…”
Section: Discussionmentioning
confidence: 99%
“…It suggested that improved cultivars of tea were valued for their higher quality. In the last dozen years, the domestication of wild C. taliensis was principally owing to the high price of wild tea that had been hyped with the cultural values and it was claimed to be produced without using pesticide and chemical fertilizers [24,26]. It is hard to believe that people were willing to abandon the improved landrace in their gardens but introduce the wild trees from the natural forests frequently during hundreds of years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genome chè đã được nghiên cứu bằng cách sử dụng các chỉ thị phân tử như chỉ thị DNA đa hình được khuếch ngẫu nhiên (RAPD-Random Amplified Polymorphic DNA) (Li et al, 2005;Lin et al, 2005;Wachira et al, 2001); chỉ thị đa hình chiều dài các đoạn DNA được khuếch đại (AFLP, Amplified Fragment Lenght Polymorphism) (Ji et al, 2009;Mishra et al, 2009;Wachira et al, 2001); chỉ thị đa hình chiều dài các đoạn cắt giới hạn (Restriction fragment length polymorphism, RFLP) (Matsumoto et al, 1994); chỉ thị dựa vào đoạn DNA lặp lại đơn giản (single sequence repeat-SSR) (Ma et al, 2010;Sahu et al, 2012;Sharma et al, 2009;Taniguchi et al, 2012;Zhao et al, 2007). Trong đó, SSR là những đoạn trình tự DNA được lặp lại liên tiếp với những nucleotide motif ngắn (1-6 bp).…”
unclassified